- - دکتر محمد نمازی (بررسی‌های حسابداری و حسابرسی, 1999)
A careful review of the literature reveals innovations and advances that have taken place in management accounting over the last decade have not been in parity with technological changes and innovations. It also reveals that in comparison with organizational and economic changes that have been experienced over the same period of time, management accounting has fallen behind.